Using smartphone technology to introduce affordable high-quality crop insurance - CGIAR Research Program on Policies, Institutions, and Markets (2017)
Low-cost insurance products that assess crop damage using pictures taken by farmers themselves through inexpensive regular smartphone cameras are being developed and tested by an IFPRI-led consortium.